A triple modality BSA-coated dendritic nanoplatform for NIR imaging, enhanced tumor penetration and anticancer therapy. Issue 19 (2nd May 2018) - Cao, Jie; Ge, Ruifen; Zhang, Min; Xia, Junfei; Han, Shangcong; Lu, Wei; Liang, Yan; Zhang, Tingting; Sun, Yong
Abstract : A simple PAMAM-based theranostic system was successfully designed for NIR imaging, deep tissue penetration and cancer therapy. Abstract : Functional theranostic systems for drug delivery capable of concurrent near-infrared (NIR) fluorescence imaging, active tumor targeting and anticancer therapies are desired for concise cancer diagnosis and treatment. Dendrimers with controllable size and surface functionalities are good candidates for such platforms. However, integration of active targeting ligands and imaging agents separately on the surface or encapsulation of the imaging agents in the inner core of the dendrimers will result in a more complex composition or reduced drug loading efficiency. Herein, we reported a PAMAM-based theranostic system, with a simple integrin-specific imaging ligand prepared from two motifs. One motif is a NIR carbocyanine fluorescent dye (Cyp) for precise in vivo monitoring of the system and identification of tumor or cancer cells, and the other is a novel tumor-penetrating cyclic peptide (CRGDKGPDC, abbreviated iRGD). BSA was non-covalently bonded with Cyp to reduce NIR agent fluorescence-quenching aggregates and enhance imaging signals. The chemotherapy effect of these dendritic systems was achieved by encapsulating paclitaxel into the hydrophobic interior of the dendrimers. In vitro and in vivo targeting and penetrating studies revealed that a significantly high amount of the dendritic systems was endocytosed by HepG2 cells and enhanced accumulation and penetration at tumor sites. Our safety evaluation showed that masking of cationic-end groups of PAMAM to neutral or anionic groups has resulted in decreased or even zero-toxicity. The preliminary antitumor efficacy of the dendritic system was evaluated. In vitro and in vivo studies confirmed that paclitaxel-encapsulated functionalized PAMAM can efficiently kill HepG2 cancer cells. In conclusion, our functionalized theranostic dendritic system could be a promising nanocarrier to effectively deliver drugs to deep tumor regions for anticancer therapy.